SOLUSI ANALITIK MASALAH KONDUKSI PANAS PADA TABUNG - Afo Rakaiwa; Suma'inna . (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2016)
In this study, we discussed the application of integral method of heat balance to solve the heat conduction problems on the cylinder analytically. In this method, function of temperature is approached by polynomials. Degree of the polynomial can be to be added but it required the additional boundary conditions that found from the governing differential equation and the basic boundary conditions. These boundary conditions are used to determine the coefficients of this polynomial. Shortcoming of this method is only applicable to cylinder which has a constant initial temperature.